El manual del dictador : por qué la mala conducta es casi siempre buena política - Bueno de Mesquita, Bruce, 1946-; Smith, Alastair, 1967- (Ojo del tiempo, 2013)
Explains the theory of political survival, particularly in cases of dictators and despotic governments, arguing that political leaders seek to stay in power using any means necessary, most commonly by attending to the interests of certain coalitions.